The Role of The Immigration Office in Tackling The Crime of Human Trafficking (Case Study at Immigration Office Class I TPI Surakarta) - Erna Putri Andriyani; K Kuswardani (Universitas Muhammadiyah Surakarta, 2024)
The role of the Immigration Office in tackling the Crime of Human Trafficking also has juridical reasons based on Law No. 21/2007 on the Eradication of the Crime of Human Trafficking. The Law on Trafficking in Persons authorizes the Immigration Office to prevent, prosecute, and restore victims of Trafficking in Persons. This research uses the empirical juridical approach method, especially on issues related to the Role of the Immigration Office in Combating Human Trafficking Crimes and to fully describe the Role of the Immigration Office in Crime of Human Trafficking in eradicating human trafficking crimes and thoroughly explain the basis for regulating the Role of the Immigration Office in Crime of Human Trafficking (TPPO) preventively in order to increase public legal awareness. The result of this research shows that Surakarta Immigration conducts socialization to the community to provide an understanding of the Crime of Human Trafficking. However, the prevention has not been effective because Immigration cannot monitor the reason behind making a visa or passport. The socialization process is conducted through social media and visits to high schools to increase public awareness.